2006
DOI: 10.1002/chin.200633233
|View full text |Cite
|
Sign up to set email alerts
|

New Aminophenoxazinones from a Marine Halomonas sp.: Fermentation, Structure Elucidation, and Biological Activity.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Furthermore, the 13 C-spectrum revealed ten quaternary C-atoms, three with a chemical shift lower than 165 ppm. With regard to the UV-spectrum of 1, with absorption maxima at 239, 259, 411 and 428 nm, strong similarities were found to the UV spectrum of 3 (237, 412 and 431 nm) [4]. Therefore, it was concluded that 1 was structurally related to 2-aminophenoxazin-3-one.…”
Section: Structure Elucidationmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the 13 C-spectrum revealed ten quaternary C-atoms, three with a chemical shift lower than 165 ppm. With regard to the UV-spectrum of 1, with absorption maxima at 239, 259, 411 and 428 nm, strong similarities were found to the UV spectrum of 3 (237, 412 and 431 nm) [4]. Therefore, it was concluded that 1 was structurally related to 2-aminophenoxazin-3-one.…”
Section: Structure Elucidationmentioning
confidence: 89%
“…It was shown that in contrast to 4 this type of aminophenoxazinone does not intercalate in DNA, but causes an arrest of the cells in the G1 phase and forces cells directly to apoptosis [24]. The recently described new aminophenoxazinones isolated from a marine Halomonas strain, 2-amino-6-hydroxyphenoxazin-3-one and 2-amino-8-benzoyl-6-hydroxyphenoxazin-3-one [4], showed moderate cytotoxic activity against different human tumor cell lines. The new aminophenoxazinones described in this paper, 1 and 2 from Streptomyces griseus Acta 2871, having an unusual substitution pattern of the core structure, exhibited a strong inhibition of human hepatocellular carcinoma cells; 2 very strongly inhibited human breast carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some new aminophenoxazinones alkaloids isolated from a marine bacteria, Halomonas sp. have shown antibacterial and cytotoxic activities against some tumor cell lines, HM02 (gastric adecocarcinoma), HepG2 (hepatocellular carcinoma) and MCF-7 (breat adecocarcinoma) [26]. Moreover, some new terpenoids, namely aspergiterpenoid A, (-)-sydonol, and (-)-sydonic acid have been isolated [27].…”
Section: Effect Of Methanol Extract and Fractions In Inhibiting Spla2mentioning
confidence: 99%